0712 CPAP Compliance: Roles Of Depressive Symptoms, Polysomnographic And Self-report Sleep Measures. (27th May 2020) - Dubrovsky, B; Inamac, A; Gikashvili, L; Weingarten, J; Cunningham, J
Abstract: Introduction: OSA poses major health risks; however, CPAP compliance is often suboptimal. Comorbid insomnia and depression contributed to poor CPAP compliance in different studies. Presently, PSG variables, self-report measures of insomnia, sleep quality and depression were tested simultaneously as predictors of compliance in new CPAP users who at 180 days of therapy had any non-zero use of CPAP. Methods: PSG-diagnosed 47 patients (18-79 y.o., 24 women) were titrated in the lab and initiated on CPAP. Compliance was assessed during days 1-30 and 151-180. For each period, percentage of days with >4hrs of CPAP use (%>4h-days30, %>4h-days180) and the average hours-per-day use (Tav30, Tav180) were measured. After regressing each compliance variable on age, sex and BMI, one at a time were tested: PSG variables from the diagnostic and titration studies, subjective reactions to CPAP after titration (sleep better vs. same/worse than usual; will vs. won't use CPAP at home), pre-treatment ISI, PSQI, ESS, and Center for Epidemiologic Studies Depression Scale-Revised (CESDR). Results: AHI ranged 6/hr-101/hr (M=24.2±19.5); %>4h-days30, 0-100% (M=68%±32%); Tav30, 0.0-9.8 hours (M=5.2±2.5); %>4h-days180, 0-100% (M=64%±34%); Tav180, 0.2-10.5 hours (M=4.7±2.8). PSG variables from both diagnostic and titration studies, reactions to CPAP, ESS and CESDR were not significant predictors of compliance (all p>0.1). ISI was marginally inversely related to %>4h-days30 (p=0.087) and Tav30 (p=0.075). Higher pre-treatment PSQI was related to lower %>4h-days30 (p=0.003, R 2 =19%) and Tav30 (p=0.011, R 2 =15%). Entered alone, PSQI was related to %>4h-days180 (p=0.042) and Tav180 (p=0.043); however, when the 1-30-day compliance was accounted for, PSQI no longer related to the 151-180-day compliance. The 1-30-day compliance strongly predicted respective 151-180-day measures (%>4h-days, p<0.001, R 2 =55%; Tav, p<0.001, R 2 =68%). Conclusion: In this limited sample of naive CPAP users, higher pre-treatment sleep disturbance reported on PSQI was a useful predictor of lower 1-30-day CPAP compliance. Neither depressive symptoms nor PSG variables from diagnostic and titration studies predicted compliance. As the initial 30-day compliance is the best predictor of later CPAP use, early interventions are crucial. Support: none